Antimony/Porous Biomass Carbon Nanocomposites as High‐Capacity Anode Materials for Sodium‐Ion Batteries. Issue 1 (29th November 2016) - Zhang, Xiaoli; Li, Pengxin; Zang, Rui; Wang, Shijian; Zhu, Ye; Li, Cong; Wang, Guoxiu
Abstract: Antimony/porous biomass carbon nanocomposites have been prepared by a chemical reduction method and applied as anodes for sodium‐ion batteries. The porous biomass carbon derived from a black fungus had a large Brunauer–Emmett–Teller (BET) surface area of 2233 m 2  g −1 in which antimony nanoparticles were uniformly distributed in the porous carbon. The as‐prepared antimony/porous biomass carbon nanocomposites exhibited a high reversible sodium storage capacity of 567 mA h g −1 at a current density of 100 mA g −1, extended cycling stability, and good rate capability. Abstract : A salt and battery : Antimony/porous biomass carbon nanocomposites were prepared by a chemical reduction method and applied as anodes for sodium‐ion batteries. The as‐prepared nanocomposites exhibited a high reversible sodium storage capacity, extended cycling stability, and good rate capability.